Network Numerical Simulation of Impulsively-Started Transient Radiation-Convection Heat and Mass Transfer in a Saturated Darcy-Forchheimer Porous Medium - Anwar Beg, O.; Zueco, J.; Takhar, H. S. S.; Beg´, T. A. A. (Nonlinear Analysis: Modelling and Control, 2008)
We study the effects of thermal radiation and porous drag forces on the natural convection heat and mass transfer of a viscous, incompressible, gray, absorbingemmitting fluid flowing past an impulsively started moving vertical plate adjacent to a non-Darcian porous regime. The governing boundary-layer equations are formulated in an (X∗, Y∗, t∗) coordinate system with appropriate boundary conditions. The Rosseland diffusion approximation is employed to analyze the radiative heat flux and is appropriate for non-scattering media. The model is non-dimensionalized and solved with the network simulation model. We study the influence of Prandtl number, radiation-conduction parameter, thermal Grashof number, species Grashof number, Schmidt number, Darcy number and Forchheimer number on the dimensionless velocity, temperature and species function distributions. Additionally we compute the variation of the local skin friction, Nusselt number and Sherwood number for selected thermophysical parameters. Increasing Darcy number is seen to accelerate the flow; the converse is apparent for an increase in Forchheimer number. Thermal radiation is seen to reduce both velocity and temperature in the boundary layer. The interactive effects of second order porous drag and thermal radiation are also considered. The model finds applications in solar energy collection systems, porous combustors, transport in fires in porous media (forest fires) and also the design of high temperature chemical process systems.
Keywords: thermal radiative heat transfer; Rosseland model; convection; mass transfer; non-Darcian regime; network numerical simulation; energy systems; Nusselt and Sherwood number